Experimental scanning electron microscopic investigation of pathological dentinogenesis in posteruptive tooth phase - Vojinović Jovan; Stevanović Radoje; Hrvaćanin Slobodanka (Serbian Medical Society - Dental Section, Belgrade, 2006)
In the article are presented results of SEM study of pathological dentinogenesis on the human and dogs tooth in the different formative stages. The pathological dentinogenesis take place in the genetically predetermined way no matter of type of an irritation. The structure of pathological dentin depends upon the level of irritation and its duration. Lower level irritation produce the secretion of tubular dentine with irregular tubular direction, higher irritation stronger irregularities. Strong irritations damage odonoblastes, and they are replaced by undifferentiated cells. Lower level of differentiation produce more irregular dentine. New cells momentarily starts secretion, at the beginning the atubular dentine, and latter tubules arrear. The odontoblasts are very resistant cells, so even under of very strong irritants some of them could survive and continue formatting individual tubules detected within amorphous dentinal tissue. The resistance of odontoblasts is limited, specially when irritations are long enough exhausting formative potential of cells. Excreted dentinal tissue becomes more and more irregular. These biological facts should be consider in the therapy of puplodentinal complex. Therapy have to preserve conditions for undisturbed recovery of damaged odontoblasts, or new undifferentiated cells. In the other words biological principles insist on the preservation of conditions for the normal expression of formative cells genetically tasks.